Planning and Strategic Management of Higher Education Considering the Vision of Latin America - Esteban Inga; Juan Inga; Jorge Cárdenas; Juan Cárdenas (MDPI AG, 2021)
Nowadays, many universities are employing metrics that are used by other countries as the focus moves towards academic management. A shared vision and collaboration is required to identify success cases. Leaders at senior and middle management need to be guided by a road map to get a clear vision, a list of different strategies and successful outcomes. Consequently, this article proposes an academic management strategy to guarantee student-centred education. This strategy has an emphasis on hierarchical process in layers, in order to optimise and achieve efficiency, reliability and resilience. In this paper, the "what", " how" and "where" are taken into account in order to respond to academic and administrative adjustments which are necessary to reduce the risk of investment in training and formation of human capital, which warns about the need to acquire knowledge, especially from countries with scientific expertise. It is also shown the indicators that motivate the effort based on the merit that human capital produces. A methodology of flipped learning or blended learning is applied to presume a human capital that is able to break down barriers, such as: English as a universal language. A bibliometric analysis has been based over 2000 scientific articles from the Web of Science and Scopus databases. So It was possible to identify countries, universities and researchers specifically for each area of knowledge based on the results of this analysis. Besides, university careers can even be validated according to the development and scientific interest that is presented by the bibliometric analysis, which could be compared with studies based on economics and wealth from sources such as Forbes.